An alternative to updating topographic maps using SPOT images - De Freitas, Maria Isabel Castreghini [UNESP] (My University, 2000)
Brazil has serious problems in systematic mapping and cartographic updating. Only 13% of the country is mapped in scale 1:50,000 and most of these maps are from approximately 30 years ago. Usually, professionals such as planners, engineers and geographers need updated documents to develop their work in regional scale. Sometimes they need to elaborate maps by themselves, using basic knowledge in Cartography and Remote Sensing applied through alternative methodologies. The main aim of this paper is to updating a 1:50,000 topographic map using SPOT-HRV panchromatic and multispectral images through a low cost methodology. The area of study corresponds to the topographic map from the region of Rio Claro, State of São Paulo, Brazil, produced by IBGE (Brazilian Institute of Geography and Statistics) in the 1:50,000 scale. The software utilized were AutoCAD R.12 and Idrisi for Windows. The methodology includes application of Digital Image Enhancement through HSI transformation in the SPOT multispectral and panchromatic images as well as techniques of visual interpretation through the GIS Idrisi. The SPOT images were registered using control points selected from topographic maps in 10,000 scale, from IGC (Geographic and Cartographic Institute) from the State of São Paulo. A preliminary verification of the updated information content was made using aerial photographs in scale 1:25,000. After that, seven fieldwork's were performed to solve doubts of the final interpretation. The comparison of the informative content performed showed the image potential to updating tasks, especially concerning to roads, watercourses and railways. Some difficulties appeared in the interpretation of the energy transmission lines, mainly due to the discontinuities in the visualization of the high-tension protection zone. The analysis of the image registration precision presented approximately the RMS equal to 34.96 m for the studied image composition, compatible with the research expectancy. The interpretation of aerial photographs and field verifying solved doubts in the updating process and had an important contribution to the final updated map. The results concerning information content highlight this alternative to updating topographic maps with low cost through an alternative methodology.
Keywords: Cartographic updating; SPOT image; Topographic map